Digital filtering of oscillations intrinsic to transmission line modeling based on lumped parameters - Da Costa, Eduardo Coelho Marques; Kurokawa, Sérgio [UNESP]; Shinoda, Ailton Akira [UNESP]; Pissolato, José (Elsevier, 2013)
A correction procedure based on digital signal processing theory is proposed to smooth the numeric oscillations in electromagnetic transient simulation results from transmission line modeling based on an equivalent representation by lumped parameters. The proposed improvement to this well-known line representation is carried out with an Finite Impulse Response (FIR) digital filter used to exclude the high-frequency components associated with the spurious numeric oscillations. To prove the efficacy of this correction method, a well-established frequency-dependent line representation using state equations is modeled with an FIR filter included in the model. The results obtained from the state-space model with and without the FIR filtering are compared with the results simulated by a line model based on distributed parameters and inverse transforms. Finally, the line model integrated with the FIR filtering is also tested and validated based on simulations that include nonlinear and time-variable elements. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Digital signal processing; Electromagnetic transients; FIR digital filter; Transmission lines; Correction method; Correction procedure; Digital filtering; Digital signals; Distributed parameter; Electro-magnetic transient; Electromagnetic transient simulation; Finite-impulse response; FIR digital filters; FIR filtering; Frequency-dependent; High frequency components; Line models; Lumped parameter; State equations; State-space models; Transmission line modeling; Electric lines; FIR filters; Impulse response; Inverse transforms; Transients; Transmission line theory; Computer simulation